Challenges and issues faced by IT industries to maintain environmental sustainability - Sarita Rathi, Ms.; Shyamalendu Niyogi, Prof.Dr.; jasvinder Kaur, Dr. (International Journal of Engineering and Technology, 2018)
Green should be implemented not only at the disposal stage of a computer and laptop but it should also be implemented at manufacturing and consumption stages. Companies like IBM, HP, HCL, Microsoft, Wipro, Cognizant etc. are working on the green design of a computer. HCL is taking many initiatives such as Green Edge, green services and green peace to reduce the effect of toxic chemicals and hazardous materials. Green Edge is a framework on which HCL is working to improve the manufacturing process of products to make them green and economically viable. TCS is reducing the impact of their and their customerâ€™s activities by adopting the 3-R strategy, which helps to reduce, reuse and recycle the waste produced by them. The goal of TCS is to achieve zero wastage till 2020. Cognizantâ€™s initiative is Go Green. Go Green is launched in 2008; its main purpose is to recycle the waste and to save and reduce energy consumption. While taking these initiatives IT industries are facing many issues and challenges to produce toxic free products. Some of those challenges and issues are discussed in the paper. Â Â